A method for preparing high entropy alloy composite microwave absorbing material
The preparation of five-member high-entropy alloy composite absorbing materials by microwave heating method solves the problems of cumbersome preparation process and long cycles in the prior art, and achieves efficient electromagnetic wave absorption performance. The preparation process is simple and low cost, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202410497978.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The preparation process of existing foam structure metal absorbing wave materials is cumbersome and has a long cycle, making it difficult to meet the needs of efficient electromagnetic wave absorption.
The microwave heating method is used to prepare five-membered high-entropy alloy composite wave absorbing materials, and the rapid preparation of high-efficiency wave absorbing materials through ball milling and water bath insulation.
It achieves rapid rise to extremely high temperature in a very short time, and forms a porous foam-like structure with a three-dimensional porous structure, significantly reduces product density, has high-efficiency electromagnetic wave absorption performance, and is simple in preparation process and low in cost, which is suitable for large-scale production.
Smart Images

Figure CN118406925B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a wave absorbing material. Background Art
[0002] The rapid development of electronic technology and other technologies in recent decades has brought about serious electromagnetic pollution problems. In order to cope with the serious harm caused by electromagnetic pollution to electronic equipment and human health, the design and research of electromagnetic absorbing and shielding materials have been advancing with the times. In-depth research on absorbing materials corresponding to communication equipment and radar bands (2-18GHz) is of great significance. Based on the research of a large number of absorbing materials of various systems, the requirements for absorbing performance are becoming more and more stringent. It is difficult for existing absorbing materials to have good special environment service capabilities while having the comprehensive performance of "thin, light, wide and strong", including high temperature environment, acidic environment, salt spray environment, etc. Since Yeh et al. proposed the concept of high entropy alloy (HEA) in 2004, research on high entropy alloys has become popular for a while. Unlike traditional alloys that only use one or two elements as the main element, high entropy alloys generally refer to multi-main element alloys composed of five or more elements with equal atomic ratios or near atomic ratios. High entropy alloys tend to form single-phase or two-phase solid solutions rather than intermediate phases. Due to the characteristics of high entropy effect, lattice distortion effect, hysteresis diffusion effect, etc. High entropy alloys have potential applications in many fields, such as wear-resistant coatings, biomedical materials, hydrogen storage materials, ship and marine engineering materials, thermoelectric materials, superconducting materials and electromagnetic materials. In recent years, high entropy alloy absorbers have also become a hot topic in the research of absorbers. Due to the large number of constituent elements of high entropy alloys, the lattice distortion effect produced will lead to a decrease in conductivity and a larger skin depth, making high entropy alloy absorbers easier to absorb electromagnetic waves. In addition, high entropy alloys are easy to generate nanocrystalline structures, which makes the improvement of absorber performance not only limited to changing the aspect ratio of alloy particles. The regulation of microstructure can enable it to obtain a larger magnetic permeability and obtain stronger absorption in the low frequency band. At the same time, the anti-corrosion and anti-oxidation properties of high entropy alloys make it possible to be used in harsh environmental conditions as a new generation of electromagnetic wave absorbers.
[0003] Metal wave-absorbing materials with foam structures are more conducive to improving the performance of absorbers. Weidong Zhang et al. used a hydrothermal method to synthesize a new nickel-based foam modified with manganese dioxide nanosheets (Ni@MnO2 NS foam). First, the purchased nickel foam was pretreated, and then potassium permanganate was used as a manganese source to immerse the nickel foam in a manganese solution for a hydrothermal reaction. The hydrothermal process is time-consuming and has a low yield, so further optimization of the process can be considered to shorten the time. Jiyuan Liang et al. used a novel ancient food process, the dough method, to prepare three-dimensional Ni foam, and grew a thin layer of NiO nanostructure on it by thermal oxidation to form NiO / Ni foam as an efficient oxygen evolution reaction (OER) electrocatalyst. In this method, nickel nitrate (II) hexahydrate was used as a nickel precursor and leavening agent, F127 was used as a "solid solvent" and fuel, and the ground mixture of nitrate and F127 powder was heated at 80°C to form a green dough, which was calcined at 300°C to produce Ni foam. NiO / Ni foam was prepared by in-situ thermal oxidation and used as an electrocatalyst for OERs. With reference to the previous method, Wu Hongjing's research group prepared a lightweight Ni foam and NiO / NiFe2O4 in-situ growth composite material through a simple and universal route as an effective alternative to high-performance metal-based electromagnetic wave absorbers. Among them, nickel foam was synthesized by the dough method, and NiO / NiFe2O4 was generated in situ on the surface of nickel foam. The biggest limitation of the above methods is that the preparation process requirements are extremely high, the preparation process is cumbersome, and the cycle is long. In order to solve this problem, the present invention prepares a five-element high entropy alloy composite absorbing material through a simple short-time microwave method, and explores a new process for the preparation of high entropy alloy absorbing materials. Summary of the invention
[0004] In order to solve the problems of complicated preparation process and long period of the existing metal wave absorbing materials with foam structure, the present invention provides a preparation method of a high entropy alloy composite wave absorbing material.
[0005] The preparation method of the high entropy alloy composite absorbing material of the present invention is carried out according to the following steps:
[0006] Step 1: Weigh the raw materials of high entropy alloy and diethylene glycol;
[0007] The raw material of the high entropy alloy is nitrate, sulfate, acetate or oxide of the high entropy alloy element;
[0008] The high entropy alloy is a five-element high entropy alloy, and the five elements of the high entropy alloy are selected from iron, cobalt, nickel, chromium, aluminum, magnesium, zinc, manganese, and copper;
[0009] The molar ratio of the five elements in the high entropy alloy is 1:1:1:1:1;
[0010] The mass ratio of the raw material of the high entropy alloy to diethylene glycol is (1-10):1;
[0011] Step 2: Put the raw material of high entropy alloy and diethylene glycol weighed in step 1 into a ball mill and perform ball milling to obtain a paste product;
[0012] The ball milling process is as follows: the ball-to-material ratio is 5-10:1, the ball milling speed is 100-500r / min, and the ball milling time is 10-60min;
[0013] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in a water bath for a period of time;
[0014] The temperature of the water bath is 30-100°C;
[0015] The time of keeping warm in the water bath is 0.5-12h;
[0016] Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy composite absorbing material; the microwave heating time is 5-20s, and the microwave power is 690-710W.
[0017] The principles and beneficial effects of the present invention are:
[0018] 1. The present invention adopts microwave heating to achieve a rapid rise to an extremely high temperature in a very short time. The mixture of metal salt and diethylene glycol decomposes and expands dozens of times to produce a large number of pores, and finally forms a porous foam structure with a three-dimensional porous structure, which effectively constructs a network channel for attenuating electromagnetic waves and greatly reduces the density of the product. Compared with bulk metal, the metal foam absorbing material with a porous foam structure effectively overcomes the inherent defects of bulk metal such as high density and impedance mismatch, and has high-efficiency electromagnetic wave absorption performance.
[0019] 2. The present invention compounds high entropy alloy and carbon. The FeCoNiCrAl transition metal high entropy alloy has good magnetic properties. Carbon is mainly used as a dielectric absorbing material. The compound of two-phase materials with dielectric loss mechanism and magnetic loss mechanism is conducive to achieving the electromagnetic wave loss mechanism of dielectric-magnetic loss synergy. The present invention pioneered the use of microwave heating to obtain high entropy alloy composite absorbing materials. Due to the short-term and high-temperature characteristics of microwave heating, carbon can serve as a three-dimensional skeleton and as a growth interface for high entropy alloy nanoparticles while the precursor rapidly expands. The large number of two-phase heterogeneous bonding interfaces contributes to dipole polarization and interface polarization effects, which has a positive effect on improving the absorbing performance of composite materials, and further improves the absorbing performance of high entropy alloys.
[0020] 3. The reflection loss value of the coating with a thickness of 2 mm prepared from the high entropy alloy composite absorbing material and paraffin wax mixture of the present invention can reach about -24.28 dB, and the effective absorption bandwidth is 4.32 GHz (specific frequency band 3.76-8.08 GHz). Its effective absorption bandwidth has significant advantages, proving its excellent comprehensive absorbing performance.
[0021] 4. The present invention can realize the preparation of high entropy alloy composite absorbing materials by only using a microwave oven, and the process does not require atmosphere protection. The microwave heating method has the advantages of short time and high efficiency, which is unmatched by the preparation methods using other equipment. The preparation process has low energy consumption, low cost, simple operation, high efficiency, no need for complex equipment, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a reflection loss diagram of the FeCoNiCrAl five-element high entropy alloy composite absorbing material prepared in Example 1;
[0023] Figure 2 This is a reflection loss diagram of the FeCoNiMgZn five-element high entropy alloy composite absorbing material prepared in Example 2;
[0024] Figure 3 This is a reflection loss diagram of the FeCoNiMnCu five-element high entropy alloy composite absorbing material prepared in Example 3;
[0025] Figure 4 This is a SEM image of the FeCoNiCrAl five-element high entropy alloy composite absorbing material prepared in Example 1; DETAILED DESCRIPTION
[0026] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0027] Specific implementation method 1: The preparation method of the high entropy alloy composite absorbing material in this implementation method is carried out according to the following steps:
[0028] Step 1: Weigh the raw materials of high entropy alloy and diethylene glycol;
[0029] The raw material of the high entropy alloy is nitrate, sulfate, acetate or oxide of the high entropy alloy element;
[0030] The mass ratio of the raw material of the high entropy alloy to diethylene glycol is (1-10):1;
[0031] Step 2: Put the raw material of high entropy alloy and diethylene glycol weighed in step 1 into a ball mill and perform ball milling to obtain a paste product;
[0032] The ball milling process is as follows: the ball-to-material ratio is 5-10:1, the ball milling speed is 100-500r / min, and the ball milling time is 10-60min;
[0033] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in a water bath for a period of time;
[0034] The temperature of the water bath is 30-100°C;
[0035] The time of keeping warm in the water bath is 0.5-12h;
[0036] Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy composite absorbing material; the microwave heating time is 5-20s, and the microwave power is 690-710W.
[0037] This implementation has the following beneficial effects:
[0038] 1. This embodiment adopts microwave heating to achieve a rapid rise to an extremely high temperature in a very short time. The mixture of metal salt and diethylene glycol decomposes and expands dozens of times to produce a large number of pores, and finally forms a porous foam structure with a three-dimensional porous structure, which effectively constructs a network channel for attenuating electromagnetic waves and greatly reduces the density of the product. Compared with bulk metal, the metal foam absorbing material with a porous foam structure effectively overcomes the inherent defects of bulk metal such as high density and impedance mismatch, and has high-efficiency electromagnetic wave absorption performance.
[0039] 2. In this embodiment, high entropy alloy and carbon are compounded. The FeCoNiCrAl transition metal high entropy alloy has good magnetic properties. Carbon is mainly used as a dielectric absorbing material. The compound of two-phase materials with dielectric loss mechanism and magnetic loss mechanism is conducive to achieving the electromagnetic wave loss mechanism of dielectric-magnetic loss synergy. This embodiment innovatively proposes to use microwave heating to obtain high entropy alloy composite absorbing materials. Due to the short-term and high-temperature characteristics of microwave heating, carbon can serve as a three-dimensional skeleton and as a growth interface of high entropy alloy nanoparticles while the precursor expands rapidly. The large number of two-phase heterogeneous bonding interfaces contributes to dipole polarization and interface polarization effects, which has a positive effect on improving the absorbing performance of composite materials, and further improves the absorbing performance of high entropy alloys.
[0040] 3. The reflection loss value of the coating with a thickness of 2 mm prepared from the mixture of the high entropy alloy composite absorbing material and paraffin in this embodiment can reach about -24.28 dB, and the effective absorption bandwidth is 4.32 GHz (specific frequency band 3.76-8.08 GHz). Its effective absorption bandwidth has significant advantages, proving its excellent comprehensive absorbing performance.
[0041] 4. This embodiment can realize the preparation of high entropy alloy composite absorbing materials by only using a microwave oven, and the process does not require atmosphere protection. The microwave heating method has the advantages of short time and high efficiency, which is unmatched by the preparation methods using other equipment. The preparation process has low energy consumption, low cost, simple operation, high efficiency, no need for complex equipment, and is conducive to large-scale production.
[0042] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the high entropy alloy described in step 1 is a five-element high entropy alloy, and the five elements of the high entropy alloy are selected from iron, cobalt, nickel, chromium, aluminum, magnesium, zinc, manganese, and copper; the molar ratio of the five elements in the high entropy alloy is 1:1:1:1:1.
[0043] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the ball milling process in step two is: the ball-to-material ratio is 6:1, the ball milling speed is 100-500r / min, and the ball milling time is 10-60min.
[0044] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that: the ball milling process in step 2 is: the ball-to-material ratio is 5-10:1, the ball milling speed is 300r / min, and the ball milling time is 10-60min.
[0045] Specific implementation method five: This implementation method is different from specific implementation methods one to four in that: the ball milling process in step two is: the ball-to-material ratio is 5-10:1, the ball milling speed is 100-500r / min, and the ball milling time is 30min.
[0046] Specific implementation method six: This implementation method is different from any one of specific implementation methods one to five in that: in step one, the mass ratio of the raw material of the high entropy alloy and diethylene glycol is 5:1.
[0047] Specific implementation method 7: This implementation method is different from any one of specific implementation methods 1 to 6 in that: the temperature of keeping warm in the water bath in step 3 is 80°C.
[0048] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that: the time for keeping warm in the water bath in step three is 6 hours.
[0049] Specific implementation method 9: This implementation method is different from any one of specific implementation methods 1 to 8 in that: the microwave heating time in step 4 is 20s, and the microwave power is 690-710W.
[0050] Specific implementation method ten: This implementation method is different from any one of specific implementation methods one to nine in that: the microwave heating time in step four is 20s, and the microwave power is 700W.
[0051] Embodiment 1:
[0052] The preparation method of the high entropy alloy composite absorbing material of this embodiment is carried out according to the following steps:
[0053] Step 1: Weigh the raw materials of high entropy alloy and diethylene glycol;
[0054] The raw materials of the high entropy alloy are ferric nitrate, cobalt nitrate, nickel nitrate, chromium trioxide and aluminum trioxide;
[0055] The molar ratio of iron, cobalt, nickel, chromium and aluminum in the high entropy alloy is 1:1:1:1:1;
[0056] The mass ratio of the raw material of the high entropy alloy to diethylene glycol is 4:1;
[0057] Step 2: Put the raw material of high entropy alloy and diethylene glycol weighed in step 1 into a ball mill and perform ball milling to obtain a paste product;
[0058] The ball milling process is as follows: the ball-to-material ratio is 5:1, the ball milling speed is 200r / min, and the ball milling time is 30min;
[0059] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in a water bath for a period of time;
[0060] The temperature of the water bath is 80°C;
[0061] The time of keeping warm in the water bath is 3h;
[0062] Step 4: After keeping warm in step 3, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy composite absorbing material; the microwave heating is for 20 seconds, and the microwave power is 700W.
[0063] Figure 1 This is the reflection loss diagram of the FeCoNiCrAl five-element high entropy alloy absorbing material prepared in Example 1. Figure 1 It can be seen that the reflection loss value of the absorber can reach about -24.28dB, and the effective absorption bandwidth is 4.32GHz (3.76-8.08GHz). Compared with the existing high entropy alloy absorbers, the absorber has a wider effective absorption bandwidth in the low frequency range, and also has better absorption performance in the high frequency range, and the electromagnetic absorption performance is more excellent. Figure 4 This is the SEM image of the FeCoNiCrAl five-element high entropy alloy absorbing material prepared in Example 1. Obvious holes can be observed in the image. The abundant holes will greatly extend the transmission path of the electromagnetic wave, and multiple reflections inside it will dissipate energy and improve the absorbing performance.
[0064] Embodiment 2:
[0065] The preparation method of the high entropy alloy composite absorbing material of this embodiment is carried out according to the following steps:
[0066] Step 1: Weigh the raw materials of high entropy alloy and diethylene glycol;
[0067] The raw materials of the high entropy alloy are ferric nitrate, cobalt nitrate, nickel nitrate, magnesium sulfate and zinc acetate;
[0068] The molar ratio of the five elements of iron, cobalt, nickel, magnesium and zinc in the high entropy alloy is 1:1:1:1:1;
[0069] The mass ratio of the raw material of the high entropy alloy to diethylene glycol is 4:1;
[0070] Step 2: Put the raw material of high entropy alloy and diethylene glycol weighed in step 1 into a ball mill and perform ball milling to obtain a paste product;
[0071] The ball milling process is as follows: the ball-to-material ratio is 7:1, the ball milling speed is 300r / min, and the ball milling time is 30min;
[0072] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in a water bath for a period of time;
[0073] The temperature of the water bath is 80°C;
[0074] The time of keeping warm in the water bath is 5 hours;
[0075] Step 4: After keeping warm in step 3, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy composite absorbing material; the microwave heating is for 20 seconds, and the microwave power is 700W.
[0076] Figure 2 This is the reflection loss diagram of the FeCoNiMgZn five-element high entropy alloy absorbing material prepared in Example 2. Figure 2 It can be seen that the reflection loss value of the absorber can reach about -10.54dB. The absorber has a relatively good absorbing performance in the low frequency range.
[0077] Embodiment 3:
[0078] The preparation method of the high entropy alloy composite absorbing material of this embodiment is carried out according to the following steps:
[0079] Step 1: Weigh the raw materials of high entropy alloy and diethylene glycol;
[0080] The raw materials of the high entropy alloy are iron nitrate, cobalt nitrate, nickel nitrate, manganese acetate and copper sulfate;
[0081] The molar ratio of iron, cobalt, nickel, manganese and copper in the high entropy alloy is 1:1:1:1:1;
[0082] The mass ratio of the raw material of the high entropy alloy to diethylene glycol is 4:1;
[0083] Step 2: Put the raw material of high entropy alloy and diethylene glycol weighed in step 1 into a ball mill and perform ball milling to obtain a paste product;
[0084] The ball milling process is as follows: the ball-to-material ratio is 7:1, the ball milling speed is 400r / min, and the ball milling time is 40min;
[0085] Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in a water bath for a period of time;
[0086] The temperature of the water bath is 80°C;
[0087] The time of keeping warm in the water bath is 6 hours;
[0088] Step 4: After keeping warm in step 3, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy composite absorbing material; the microwave heating is for 20 seconds, and the microwave power is 700W.
[0089] Figure 3 This is the reflection loss diagram of the FeCoNiMnCu five-element high entropy alloy absorbing material prepared in Example 3. Figure 3 It can be seen that the reflection loss value of the absorber can reach about -14.57dB, and it has good absorbing performance in the low frequency range.
Claims
1. A method for preparing a high entropy alloy composite absorbing material, characterized in that: The preparation method of the high entropy alloy composite absorbing material is carried out according to the following steps: Step 1: Weigh the raw materials of high entropy alloy and diethylene glycol; The raw material of the high entropy alloy is nitrate, sulfate, acetate or oxide of the high entropy alloy element; The mass ratio of the raw material of the high entropy alloy to diethylene glycol is (1-10):1; The high entropy alloy is a five-element high entropy alloy, and the five elements of the high entropy alloy are selected from iron, cobalt, nickel, chromium, aluminum, magnesium, zinc, manganese, and copper; the molar ratio of the five elements in the high entropy alloy is 1:1:1:1:1; Step 2: Put the raw material of high entropy alloy and diethylene glycol weighed in step 1 into a ball mill and perform ball milling to obtain a paste product; The ball milling process is as follows: the ball-to-material ratio is 5-10:1, the ball milling speed is 100-500r / min, and the ball milling time is 10-60min; Step 3: Transfer the paste product obtained in step 2 into a quartz crucible, and then keep it in a water bath for a period of time; The temperature of the water bath is 30-100°C; The time of keeping warm in the water bath is 0.5-12h; Step 4: After the step 3 is kept warm, the quartz crucible is transferred to a microwave oven for heating to obtain a high entropy alloy composite absorbing material; the microwave heating time is 5-20s, and the microwave power is 690-710W.
2. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The ball milling process in step 2 is as follows: the ball-to-material ratio is 6:1, the ball milling speed is 100-500r / min, and the ball milling time is 10-60min.
3. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The ball milling process in step 2 is as follows: the ball-to-material ratio is 5-10:1, the ball milling speed is 300r / min, and the ball milling time is 10-60min.
4. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The ball milling process in step 2 is as follows: the ball-to-material ratio is 5-10:1, the ball milling speed is 100-500r / min, and the ball milling time is 30min.
5. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The mass ratio of the raw material of the high entropy alloy and diethylene glycol in step 1 is 5:
1.
6. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The temperature of keeping warm in the water bath in step 3 is 80°C.
7. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The time of keeping warm in the water bath as described in step 3 is 6 hours.
8. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The microwave heating time in step 4 is 20s, and the microwave power is 690-710W.
9. The method for preparing a high entropy alloy composite absorbing material according to claim 1, characterized in that: The microwave heating time in step 4 is 20s, and the microwave power is 700W.
Citation Information
Patent Citations
Solvent-free type three-dimensional metal nanofoam and preparation method thereof
CN106498217A
Three-dimensional intercommunicated reticular heat-conducting and wave-absorbing foam material as well as preparation method and application thereof
CN116333684A